1995
DOI: 10.1017/s0143385700008403
|View full text |Cite
|
Sign up to set email alerts
|

A note on transitive flows

Abstract: In this article, we study transitive flows on manifolds or on manifold-like phase spaces. These are flows in which at least one orbit is dense. By quantifying the nature of the set of dense orbits, a variety of transitivity types is obtained. We explore conditions under which products or 'scaled' products of transitive flows are again transitive. We also investigate a connection between transitivity and topologically strong mixing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…An extremely interesting question concerns the existence and behavior of scattering amplitudes for processes where particles "pass through" the singularity. This is the situation studied in [4,6,7,8,9,10,11,12,13,14,32]. The conclusion of this work, [8] in particular, is that such scattering amplitudes are badly behaved in string perturbation theory.…”
Section: Defining Scattering Through the Singularitymentioning
confidence: 70%
See 2 more Smart Citations
“…An extremely interesting question concerns the existence and behavior of scattering amplitudes for processes where particles "pass through" the singularity. This is the situation studied in [4,6,7,8,9,10,11,12,13,14,32]. The conclusion of this work, [8] in particular, is that such scattering amplitudes are badly behaved in string perturbation theory.…”
Section: Defining Scattering Through the Singularitymentioning
confidence: 70%
“…In the examples of cosmological singularities constructed as time dependent orbifolds of Minkowski space, the work of [8] showed that tree level amplitudes diverge, due to infinite blueshifts at the singularities. References [13,14] discussed the physical meaning of these results and argued that in general nonperturbative phenomena should be expected around such points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is what happens here too. From (5.34), the frequencies are 35) which are just the expected Matsubara frequencies. 6 Note also that…”
Section: Two-point Functionsmentioning
confidence: 81%
“…Next, we focussed on the massless BTZ black hole background, because of its simplicity, supersymmetry, its connection to pure AdS 3 , and its relation to recent attempts to study cosmological backgrounds in string theory (see e.g. [32][46] [47][48] [49] for references closest to our work). By taking the global structure of the space properly into account, and using a classical analysis of wound strings, we argued that the proposal for a ghost free spectrum of [38] finds a natural interpretation as pertaining to strings on the massless black hole background.…”
Section: Discussionmentioning
confidence: 99%